2021
DOI: 10.1590/1984-3143-ar2020-0213
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how environmental factors influence reproductive aspects of wild myomorphic and hystricomorphic rodents

Abstract: Myomorphic and hystricomorphic rodents are vital for maintaining various ecosystems around the planet. This review enables a better understanding of how these rodents respond to environmental factors and adapt to climate adversities. Innumerable factors, such as photoperiod, rainfall, and temperature, can impair or contribute to the quality of rodent reproductive parameters. Prolonged animal exposure to high ambient temperatures alters thermoregulation mechanisms and causes testicular and ovarian tissue degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Thus, further studies are necessary to gain insight into the triangle of Rodent–Flea– Bartonella . The climate condition in summer is not only suitable for rodent reproduction and movement (Dantas et al., 2021; Hosseini et al., 2004) but also easy to cause human skin exposure (most people often wear shorts and shirts). In addition, our study discovered a high prevalence rate in the summer, all of which enhance the likelihood of human contact with rodents and rodent fleas, thus increasing the risk of Bartonella transmission to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, further studies are necessary to gain insight into the triangle of Rodent–Flea– Bartonella . The climate condition in summer is not only suitable for rodent reproduction and movement (Dantas et al., 2021; Hosseini et al., 2004) but also easy to cause human skin exposure (most people often wear shorts and shirts). In addition, our study discovered a high prevalence rate in the summer, all of which enhance the likelihood of human contact with rodents and rodent fleas, thus increasing the risk of Bartonella transmission to humans.…”
Section: Discussionmentioning
confidence: 99%
“…dough, preharvest stage and lean period when the temperature was high as well as when the day length increased. Dantas et al (2021) reported that environmental factors such as photoperiod, temperature and rainfall could impair or contribute to the quality of reproductive parameters of rodents.…”
Section: Resultsmentioning
confidence: 99%
“…Rodent reproduction is influenced by a variety of environmental factors, including photoperiod [16], rainfall [17][18][19], temperature [18,20,21] and temperature (Sarli e In order to identify the physiological and behavioural responses of these animals and develop mitigation strategies for the negative effects on reproductive activity, whether brought on by climate change or intentionally harmful human actions to ecosystems, it is crucial to understand how these environmental factors affect rodents.…”
Section: Copyright© Akunna Ggmentioning
confidence: 99%